Saving the Chinese Ghosts Overseas: A Study of the Yogacara Ulkā-Mukha Ritual in Thailand - Liu, Yaoping; Du, Wenchen (Millah: Journal of Religious Studies, 2025)
Currently, the most common methods for preserving supernatural beings from foreign lands involve conducting religious ceremonies and beseeching spiritual creatures in close proximity. This inquiry aims to explore the spiritual significance and function of the Yogacara Ulkā-Mukha ritual practices in the redemption of Chinese spirits that are residing abroad. The research design employed a phenomenological approach, involving nine monks in Thailand as participants. The data-gathering process involved conducting in-depth interviews and engaging in participant observations. Subsequently, the data were subjected to thematic analysis to ascertain the significance and function of the difficulties in the execution of the ritual. The study yielded three significant findings: first, the Yogacara Ulkā-mukha ritual embodies the concept of Buddhist compassion and the duty to rescue wandering souls in their quest for tranquility; second, it explores the adaptation and challenges faced in preserving tradition and cultural heritage within the modern context; and third, it examines the potency of intention and prayer in transcending the constraints of space and time. These findings are elaborated in the concluding section of this paper. Moreover, this study suggests the creation of a ritual adaptation model that considers the use of technology to enhance the participation of overseas Chinese communities in preserving spiritual customs.